Medical infrared thermography as hidradenitis suppurativa diagnostic tool: literature review - Mazeika, Erikas; Jariene, Vaiva; Valiukeviciene, Skaidra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Hidradenitis suppurativa (HS) is a rare, chronic, inflammatory skin disease that has a strong impact on the quality of life. Medical infrared thermography (MIT) is a non-invasive imaging method that could be used for evaluation of skin inflammation, which is an important biomarker in HS. We performed a comprehensive review of the literature to verify the possibilities of using MIT for HS. Key words “hidradenitis suppurativa”, “acne inversa” and “thermography” were used for PubMed, Embase and Scopus literature analysis and in total four articles fulfilled the inclusion criteria. The inflamed areas have shown the increase in temperature (34.3°C) and after the removal of lesions the temperature has become similar to the healthy skin sites. The margins of the inflammatory lesions identified by MIT were used in the surgical treatment. Also, MIT was used in combination with other imaging tests for inflammation evaluation. Thermography is an advantageous tool to detect inflammation and to secure the success of surgical treatment.